Reliability testing of inertial measurement units in the analysis of physiological variables in archery - Zahari, Taha; Rabiu Muazu, Musa; M.R., Abdullah; M. H. A., Hassan; M. A. M., Razman; Anwar, P. P. Abdul Majeed (Centre for Advanced Research on Energy (CARe), 2017)
Archery is a static sport, detection of any movement b beneficial in ensuring shooting accuracy. Thus, determining the reliability of any detection instrument is paramount, This study aims to ascertain the postural balance. hand movement, muscular activation as well as heart rate of an archer using Shimmer sensors, An archer was observed over two different tests (A&B). Tesl A with free movement while B with restricted movement. Kolmogororv/Smirnov test was utilized to measure the reliability of the sensors over test re-test in two different tests. The Knolmogorow/Smirnov test re-test reveals a significant difference between all the indicator in both tests A and B, p < 0.001 IMUs sensors. appear to be reliable in measuring some physiological indicators in the sport of archery.